Disability status, intimate partner violence and perceived social support among married women in three districts of the Terai region of Nepal. Issue 5 (31st October 2018) - Gupta, Jhumka; Cardoso, Lauren F; Ferguson, Gemma; Shrestha, Binita; Shrestha, Prabin Nanicha; Harris, Courtney; Groce, Nora; Clark, Cari Jo
Abstract : Introduction: Women living with disabilities are disproportionately vulnerable to intimate partner violence (IPV). Existing research on the topic largely takes place in high-income settings and treats disability as a dichotomous experience—an individual either has a disability or does not. Disability experiences, however, are diverse such that some individuals face minimal impairment, while for others impairment can be severe. With this spectrum in mind, this study sought to examine the associations between severity of disability impairment, past-year IPV, past-year in-law violence and perceived social support among married women in Nepal. Methods: Baseline data (2016) from a randomised controlled trial aiming to reduce IPV among women aged 18–49 (n=1800) were analysed using generalised estimating equations logistic regressions to assess associations. Results: Women with severe impairment reported higher levels of physical and/or sexual, emotional, economic and in-law violence than women without a disability (adjusted OR (AOR)=1.68, 95% CI 1.04 to 2.72; AOR=1.65, 95% CI 1.03 to 2.65; AOR=1.75, 95% CI 1.02 to 3.02; AOR=2.80, 95% CI 2.53 to 5.11, respectively). Differences in IPV between women reporting some impairment versus no disability were observed for economic (AOR=1.47, 95% CI 1.11 to 1.94) and in-law violence (AOR=1.50, 95% CI 1.07 to 2.10). Women with severe or some impairment versus no disability were less likely to perceive their in-laws as supportive. Conclusion: Disability status was associated with increased vulnerability to IPV. A gradient was observed; the highest levels of IPV were experienced by women with severe impairment, followed by some impairment. Future research should examine the mechanisms driving such observations.